Case Report: Life-threatening cisplatin-induced myelosuppression in pediatric osteosarcoma: molecular mechanisms, pharmacogenomic profiling, and targeted clinical management - Dai, Chuanqiang; Zhang, Youshu; Zhang, Yao; Dong, Yao (Frontiers in Pharmacology, 2025)
A 10-year-old female with osteoblastic osteosarcoma developed life-threatening cisplatin-induced myelosuppression (grade IV neutropenia/thrombocytopenia) following the eighth cycle of MAP chemotherapy. Critical pharmacological findings include a cumulative cisplatin dose of 720 mg/m2exceeding the pediatric safety threshold of 400 mg/m2. The CYP3A5*1/*1 genotype prolonged the half-life of cisplatin to 8.2 h. Cisplatin-specific biomarkers included serum magnesium 1.2 mg/dL and urinary N-acetyl-β-D-glucosaminidase 48 U/L. Targeted interventions (G-CSF, romiplostim, meropenem) led to hematological recovery within 14 days. This case implicates cisplatin overdose with impaired metabolic clearance as the primary toxicity mechanism.